Assessing influences on social vulnerability to wildfire using surveys, spatial data and wildfire simulations. (1st May 2018) - Paveglio, Travis B.; Edgeley, Catrin M.; Stasiewicz, Amanda M.
Abstract: A growing body of research focuses on identifying patterns among human populations most at risk from hazards such as wildfire and the factors that help explain performance of mitigations that can help reduce that risk. Emerging policy surrounding wildfire management emphasizes the need to better understand such social vulnerability—or human populations' potential exposure to and sensitivity from wildfire-related impacts, including their ability to reduce negative impacts from the hazard. Studies of social vulnerability to wildfire often pair secondary demographic data with a variety of vegetation and wildfire simulation models to map potential risk. However, many of the assumptions made by those researchers about the demographic, spatial or perceptual factors that influence social vulnerability to wildfire have not been fully evaluated or tested against objective measures of potential wildfire risk. The research presented here utilizes self-reported surveys, GIS data, and wildfire simulations to test the relationships between select perceptual, demographic, and property characteristics of property owners against empirically simulated metrics for potential wildfire related damages or exposure. We also evaluate how those characteristics relate to property owners' performance of mitigations or support for fire management. Our results suggest that parcel characteristics provide the most significant explanation of variability in wildfire exposure, sensitivity and overall wildfire risk, while the positive relationship between income or property values and components of social vulnerability stands in contrast to typical assumptions from existing literature. Respondents' views about agency or government management helped explain a significant amount of variance in wildfire sensitivity, while the importance of wildfire risk in selecting a residence was an important influence on mitigation action. We use these and other results from our effort to discuss updated considerations for determining social vulnerability to wildfire and articulate alternative means to collect such information. Highlights: We assess wildfire vulnerability with surveys, risk simulations, and spatial data. Parcel characteristics best explain variance in exposure, sensitivity, and risk. Resident views about fire management explain variance in sensitivity. Components of exposure, risk and adaptive capacity vary at small scales. Indicators of adaptive capacity are inconsistent across levels of mitigation.